Xylem versus phloem in secondary growth: a balancing act mediated by gibberellins. (4th May 2021) - Carlsbecker, Annelie; Augstein, Frauke
Abstract : This article comments on: Ben-Targem M, Ripper D, Bayer M, Ragni L. 2021 . Auxin and gibberellin signaling cross-talk promotes hypocotyl xylem expansion and cambium homeostasis. Journal of Experimental Botany 72, 3647–3660 .